The Culture and Customs of Saqaliba in Ibn Faḍlān's Siāhat-Nāme (Travel Narrative) 921 - Tofiq, Jihad Nuri; Ali, Nariman Abdalla (El Tarikh : Journal of History, Culture and Islamic Civilization, 2023)
All the journeys and tours aimed at gaining knowledge about other peoples and lands seem to have achieved the set goals. Those who have tried to have a successful trip, have never ignored the upshot of their trip, but have benefited from the results and experiences and presented them to others in the form of a travelogue. One can argue that the product of the account of these travelogues seems to be most of the concepts related to unity and human relations and the necessity to understand other societies.This research aims to investigate one of the travelogues written in the Abbasid era (656-1258), in the 10th century, namely, Ibn Faḍlan’s travelogue, which is the product of a journey to the lands of the Persians, Turks, Saqaliba, and Khazars. To this end, in the first section, using the analytical method, the course of and reasons for his journey as well as its effects will be discussed. Then, based on the analytical and comparative method, the second section deals with the Saqaliba and their role in the region, as well as relevant texts focusing on the culture and tradition of the Saqaliba and their classification.According to the findings of this research, it was Ibn Faḍlan who for the first time, provided information about Saqaliba and their relations with Bulgaria and the Slavic race. More importantly, as a political envoy, apart from his special mission, which was to promote Islam and announce the Caliph's support for Saqaliba against the Khazars, he gives an account of the culture and customs in Europe and non-Muslim countries to the Muslims and the Caliph. This report is actually the first account of European non-Muslim customs given to the caliphate system.